Pictorial Heritage of Vyacheslav Afonichev in the Process of St. Petersburg Neoexpressionist Development - Shishkova, Polina A. (Actual Problems of Theory and History of Art, 2014)
The article covers the artistic processes of 1970–1990’s in the nonconformistic art. During these years a community of artists striving for continuation of expressionist traditions was formed in Leningrad.  Philosophical and stylistic tendencies of underground neo-expressionism development are examined on the art works of V. Afonichev (1946–2012) — an artist who managed to embody the timeless tragedy into powerful generalized images. The artist’s allegorical language, his mythological creativity and originality are analyzed here. The article tells about stylistic and conceptual innovations in the creative heritage of Afonichev and spiritual and formative elements in his art. A parallel with the Arefi ev circle and the group «Chronicle» is drawn in the article. The art works of Petersburg artist V. Afonichev are kept in museum collections. A close study of his work is very timely because it touches upon a broad spectrum of problems dealing with the formation and development of Russian neo-expressionism in the context of the world artistic culture. The creative work of V. Afonichev is a new, unexplored stage in the history of art.
Keywords: Vyacheslav Afonichev; expressionism; neo-expressionism; underground; modern painter